Fluid dynamic behaviour of four grains in two models of fluidised bed dryers (Nexo Revista Científica, 2021)
The fluid dynamic behaviour of four grains (sorghum, bean, rice, and corn) was studied in two laboratory-scale dryers: a fluidised bed and a spouted bed. The dryers consist of a transparent plastic column to which two different bases were adapted, one for each dryer, connected to a blower. Additionally, the physical properties (diameter, sphericity and bulk density) associated with fluidisation were experimentally determined as a function of grain moisture. Furthermore, the bed porosity was calculated for each of the grains at maximum moisture. It was only possible to fluidise the four grains in the spouted bed. This fluid dynamic study is the first advance in determining the physical and fluidisation properties of the most consumed grains in Nicaragua.